Assurer la maitrise du ruissellement grâce aux zones humides au voisinage des infrastructures de transport dans une perspective de conservation de la biodiversité - Camille Fressignac; Pascal Breil; Yannick Matillon; Andréa Nullans; Blandine Chazelle; Benoît Sarrazin; Dominique Vallod (VertigO)
The conservation of biodiversity is currently a major problem which is gradually inserted into the development of public policy of administrative territory, with the aim of controlling the impact of human activity on the natural environment. Land transport infrastructure creates disruptions to ecosystems and landscapes. The exploratory project RIZHU (intense runoff and wetlands), is to assess the conditions of coexistence of land transport infrastructure with that of the wetlands.The hypothesis is that a redesigned management of runoff water in the vicinity of the linear land transport infrastructure may help to restore a wetland mesh which conditions their interconnection. The feasibility of this hypothesis is tested and discussed in this article in order to bring the designer and the developer to consider this opportunity.The article recalls the conditions of existence, types and roles of wetlands. It then introduces the approach of the success factors which are: (1) convince the designer and the operator of the appropriateness of a redesigned management of storm water and (2) to benefit from operational space methods for the detection and evaluation of favorable hydrological and ecological contexts within landscapes. An illustration of these aspects is presented in a section of the TGV Méditerranée processed using a GIS tool under development at Irstea and SNCF.The tested indicators still need to be improved to achieve a tool able to assist the decision facing the variety of storm water management situations on the land transport system. Nevertheless, this initial feasibility study presents real opportunities as it combines the issues of water security and continuity of the ecological corridor of wetlands.